A nomogram predicting 30-day mortality in patients undergoing percutaneous coronary intervention - Song, Jingjing; Liu, Yupeng; Wang, Wenyao; Chen, Jing; Yang, Jie; Wen, Jun; Gao, Jun; Shao, Chunli; Tang, Yi-Da (Frontiers in Cardiovascular Medicine, 2022)
Background & Aims: Early detection of mortality after percutaneous coronary intervention (PCI) is crucial, whereas most risk prediction models are based on outdated cohorts before 2000. This study aims to establish a nomogram predicting 30-day mortality after PCI. Methods: Totally 10444 patients undergoing PCI in National Center for Cardiovascular Diseases in China were enrolled to establish a nomogram to predict 30-day mortality after PCI. The nomogram was generated by incorporating parameters selected by logistic regression with stepwise backward method. Results: Five features were selected to build the nomogram, including age, male sex, cardiac dysfunction, STEMI and TIMI0-2 after PCI. The performance of the nomogram was evaluated and the area under the curves (AUC) was 0.881(95% CI: 0.8-0.961). Our nomogram exhibited a better performance than a previous risk model (AUC=0.7, 95% CI: 0.586-0.813) established by Brener et al. And the survival curve successfully stratified the patients above and below the median score of 4. Conclusion: A novel nomogram for predicting 30-day mortality was established in unselected patients undergoing PCI, which may help risk stratification of patients in clinical practice.